REKONFIGURASI PENYULANG KINTAMANI UNTUK MENURUNKAN.RUGI-RUGI.DAYA.DAN JATUH TEGANGAN PADA WILAYAH KERJA ULP BANGLI - Juliartawan, Putu; Setiawan, I Nyoman; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
The Kintamani supplay is uone of the feedersl in the PT PLN (Persero) UP3 East Bali Work Area which is the responsibility of ULP Bangli. This feeder uses a loop type configuration that serves consumers in the Penelokan, Songan, Kintamani, Writing, Catur and Sukawana areas. This feeder has a channel length of 237,886 kms with a total distribution substation of 183 transformer units and the peak load of this feeder reaches 3,160 kW. This condition causes a voltage drop of 7.68% and power losses of 7.5%. The reconfiguration of this feeder is done by cutting the network which is transferred to Nandini's feeder. Reconfiguration by cutting the network shows an improvement in the voltage of the Kintamani feeder which initially dropped from 7.68% to 3.27% and decreased power losses from 7.5% to 4.81%. Improvements in voltage and power losses that occur in this feeder change the value of the voltage drop and power losses on the Nandini feeder, which has an increase in the percentage of voltage drop from (-)1.44% to 1.27% and losses the initial power of 0.5% to 2.10%. With this the Kintamani feeder is right for reconfiguration with the Nandini feeder. Thus, for the Kintamani feeder and the Nandini feeder, it is in accordance with the 2017-2022 Distribution System Master Plan Manual, where the maximum allowable voltage drop is a maximum of 19kV and a maximum power loss of 5%.